2021
DOI: 10.1002/uog.23606
|View full text |Cite
|
Sign up to set email alerts
|

Twin chorionicity‐specific population birth‐weight charts adjusted for estimated fetal weight

Abstract: Twin chorionicity-specific population birth-weight charts developed with adjustment for estimated fetal weight

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…while birth‐weight centiles were assessed using the singleton standard reported by Nicolaides et al 14 . and twin chorionicity‐specific reference standards reported by Briffa et al 12 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…while birth‐weight centiles were assessed using the singleton standard reported by Nicolaides et al 14 . and twin chorionicity‐specific reference standards reported by Briffa et al 12 …”
Section: Methodsmentioning
confidence: 99%
“…EFW was calculated using Hadlock's formula, including the following biometric parameters: head circumference, biparietal diameter, abdominal circumference and femur length 19 . EFW centiles were calculated using the singleton chart of Nicolaides et al 14 and the twin chorionicity-specific charts of Stirrup et al 13 , while birth-weight centiles were assessed using the singleton standard reported by Nicolaides et al 14 and twin chorionicity-specific reference standards reported by Briffa et al 12 . Fetuses with EFW less than the 10 th centile and neonates with birth weight less than the 10 th centile were defined as SGA.…”
Section: Study Population and Data Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The centiles of EFW were calculated adopting the singleton chart by Nicolaides et al [17] and the twin charts by Stirrup et al [9]. The BW centiles were assessed using the singleton standard reported by Nicolaides et al [17] and twin chorionicity-specific reference standards reported by Briffa et al [24]. Fetuses with EFW less than 10th centile and newborns with BW less than 10th centile were considered SGA.…”
Section: Study Variables and Outcomesmentioning
confidence: 99%
“…Twins are known to have lower birth weight than singletons 24 , and due to their higher risk of perinatal complications, in particular FGR, more stringent surveillance using ultrasound is required 25,26 . Recent research has found that twins have a different growth trajectory than singletons, with growth being lower from 30 weeks in DC twins compared to singletons, and MC twins being generally smaller than both DC twins and singletons throughout gestation 27,28 . Yet, current practice continues to use singleton growth charts in twins, which can lead to overdiagnosis of FGR and unnecessary iatrogenic preterm delivery.…”
Section: Assessment Of Fetal Growthmentioning
confidence: 99%